Survey on awareness and understanding on goods and services tax - Abdul Rahim, Noor Azreen Shahirah; Mohd Asrah, Norhaidah (Penerbit UTHM, 2020)
The purpose of this study is to determine the level of public awareness on the implementation of good and services tax (GST) and public understanding on issues of GST. The data was collected from citizens in Parit Raja, Batu Pahat. The methods applied for this study are descriptive statistics, Chi-square test, Cramer’s Contingency Coefficient test and Kruskal-Wallis test. The results from this study show that majority of the respondents, aware about the GST but their understanding about GST is low.